2014
DOI: 10.2478/jos-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficiency of Methods to Recruit Asian Research Participants

Abstract: Few empirical studies have evaluated the efficiency of recruitment methods to recruit nonEnglish-speaking research participants. We attempt to fill this research gap by conducting a systematic evaluation using recruitment data from a large cognitive testing study that pretested the translations of the American Community Survey. In our study we contacted 1,084 Chinese and Korean speakers to identify those who spoke little or no English. We measured the efficiency of the recruitment methods (newspaper advertisem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Cost savings are another potential advantage because recruiters usually spend more time, resources, and efforts to recruit these greater difficulty participants (nonEnglish-speaking older participants with lower education levels). Park and Sha (2014) reported that recruiting these population groups was particularly costly as they were extremely cautious about participating because surveys or cognitive interviews could be unfamiliar to them. Additionally, they often did not trust the recruitment message and were afraid of being victims of scams or they did not feel competent enough to judge the authenticity of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost savings are another potential advantage because recruiters usually spend more time, resources, and efforts to recruit these greater difficulty participants (nonEnglish-speaking older participants with lower education levels). Park and Sha (2014) reported that recruiting these population groups was particularly costly as they were extremely cautious about participating because surveys or cognitive interviews could be unfamiliar to them. Additionally, they often did not trust the recruitment message and were afraid of being victims of scams or they did not feel competent enough to judge the authenticity of the study.…”
Section: Discussionmentioning
confidence: 99%
“…As Willis (2005) noted, participant recruitment determines the feasibility of a cognitive interview study. Although several recent studies examined issues related to interview participant selection, including the impact of sample size in cognitive interviews (Blair and Conrad 2011) and how to best recruit cognitive interview participants (Ackerman and Blair 2006;Park and Sha 2014), few research studies have offered guidelines to optimize and define the participant selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…While strategies for recruiting racial and ethnic minority participants have been well documented (e.g., Horowitz et al 2009;Maxwell et al 2005;Reed et al 2003;Roosa et al 2008), the recruitment of limited English speakers has not been studied as extensively. Recent literature suggests that Asians who speak little or no English are hard to recruit because of a general lack of experience participating in surveys or social science research (Park and Sha 2014). As a result, there was distrust toward the recruiter and the study.…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of non-English-speaking populations has not been studied as extensively. Liu et al (2013) and Park and Sha (2014) conducted systematic analysis of recruitment data of Asian research participants who speak little or no English. They examined the efficiency of four common methods for recruiting research participants: newspaper ads, physical flyers, online communication, and word-of-mouth.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Although we are not aware of studies that demonstrate to what extent Asians have been underrepresented in research studies, literature shows that Asians who have limited English language proficiency are hard to recruit because of a general lack of experience participating in survey and social science research, sociocultural differences, and mistrust (Park and Sha 2014). Tailoring the recruitment methods according to the recruits' demographics may help with recruiting these hard-to-reach Asians with limited English language proficiency.…”
Section: Background and Introductionmentioning
confidence: 99%